Pelatihan Pembuatan Media Pembelajaran Berbasis Screencast-O-Matic Untuk Guru Sekolah Dasar - Apit Fathurohman; Muhammad Yusuf; Esti Susiloningsih; Abidin Pasaribu; Lintang Auliya Kurdiati; Kistiono (Ilin Institute, 2023)
The low skill of teachers in making Learning Resources and Media in Indonesia as well as in Pulau Beringin District makes the quality of learning not optimal. This community service is an effort to increase teacher professionalism (Soft Skill) in making Screenscast-O-Matic-based learning media. The purpose of implementing community service is to increase the understanding d skills of teachers in making Screenscant-O-Matic-based learning media as learning resources and media for learning both online and offline. Socialization, instruction, practice, mentorship, and assessment are the methods of this community service. This training material is delivered in two phases, with the first stage concentrating primarily on supplying knowledge on items linked to the role of learning media, their use, and their use in both online and traditional classroom settings. The second stage of training focused on making learning media using Screencast-O-Matic. The target audience in this service are elementary school teachers in Pulau Beringin District, South Ogan Komering Ulu Regency (OKUS) both from public schools and from private schools. Participants of the community service program training were very satisfied with the training in making Screencast-O-Matic-based learning media.